2014
DOI: 10.1096/fj.13-239053
|View full text |Cite
|
Sign up to set email alerts
|

Syncytin proteins incorporated in placenta exosomes are important for cell uptake and show variation in abundance in serum exosomes from patients with preeclampsia

Abstract: Exosomes are extracellular vesicles that mediate intercellular communication and are involved in several biological processes. The objective of our study was to determine whether endogenous retrovirus group WE, member l (ERVWE1)/syncytin-1 and endogenous retrovirus group FRD, member 1 (ERVFRDE1)/syncytin-2, encoded by human endogenous retrovirus (HERV) envelope (env) genes, are present at the surface of exosomes produced by placenta-derived villous cytotrophoblasts and whether they play a role in cellular upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(159 citation statements)
references
References 56 publications
5
149
0
5
Order By: Relevance
“…This suggests that an internal receptor may mediate fusion. Moreover, circulating syncytin 2 is reduced in circulating exosomes isolated from women with preeclampsia, a placental pathology specific to the human species and that can culminate in maternal and perinatal morbidity (105). Finally, both syncytin 1 and 2 are downregulated in placentas from pregnant women, suggesting placental exosomes may have a physiological role in human placental morphogenesis (78).…”
Section: A Molecular Viral Toolbox For Ev Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that an internal receptor may mediate fusion. Moreover, circulating syncytin 2 is reduced in circulating exosomes isolated from women with preeclampsia, a placental pathology specific to the human species and that can culminate in maternal and perinatal morbidity (105). Finally, both syncytin 1 and 2 are downregulated in placentas from pregnant women, suggesting placental exosomes may have a physiological role in human placental morphogenesis (78).…”
Section: A Molecular Viral Toolbox For Ev Fusionmentioning
confidence: 99%
“…Blocking endocytic pathways partially inhibits EV uptake (34,127). Villous trophoblast-derived exosomes seem to incorporate syncytins 1 and 2, which could facilitate endocytosis of these EVs (78,103,105). subunit of clathrin adaptor complex AP2, all resulting in significant decrease in exosome uptake by PC12 cells (127).…”
Section: Figmentioning
confidence: 99%
“…PE is diagnosed based on arterial hypertension and proteinuria in pregnancy (Wilson et al 2003). Many reports have shown decreased expression and aberrant localization of syncytin 1 in PE placentas compared with healthy controls (Lee et al 2001, Chen et al 2006, Langbein et al 2008, Vargas et al 2014, Zhuang et al 2014. Chiang et al (2009) showed decreased levels of GCM1, syncytin 1 and placental growth factor, which are all crucial for syncytiotrophoblast formation and placental vasculogenesis in PE placentas.…”
Section: Syncytin 1 (Herv-w; Ervw-1) and Human Placentationmentioning
confidence: 99%
“…In another study it was identified that placental cytotrophoblasts derived exosomes carry syncytin proteins that were responsible for increased cellular uptake and fusion to form the syncytiotrophoblast cells and contribute to proper establishment of uteroplacental circulation during pregnancy. However, this syncytin protein was less abundant in pregnant women's circulation who developed preeclampsia compared to those who went through uncomplicated pregnancies [76].…”
Section: Placental-derived Exosomes In Maternal Circulationmentioning
confidence: 88%
“…Firstly, placental exosomes containing protein syncytin contributes to fusion of cytotrophoblast cells to form syncytiotrophoblast cells that are necessary for syncytiotrophoblast cells' invasion into the maternal uterine spiral arterioles [75,76]. Another study reported that exosomes secreted from the extravillous trophoblast cells promote vascular smooth muscle cell migration which is particularly helpful for maternal uterine spiral arterial remodelling and properly controlled placentation [77].…”
Section: Placental Exosomal Biomolecules: Role In Placental and Matermentioning
confidence: 99%